PEREKONOMIAN MASYARAKAT PETANI DI DESA SARANG HALANG KECAMATAN SUNGAI RAYA KABUPATEN HULU SUNGAI SELATAN - Ety Widiyati (JURNAL SOCIUS, 2015)
Many people in Desa Sarang Halang, Sungai Raya work on farms and plantations. Information from the location tells that the level of irregular incomes from farming or gardening is sometimes unpredictable. This happens due to failure in harvesting caused by rats and red seeds. In addition, limited capital and land ownership become the problems for the farming community. Therefore, the lives of the farmers in the village are quite alarming because the agricultural produce is just enough for their daily needs and is not even sufficient for paying the children’s needs for their schools. The results of the study showed that they still used simple tools for farming. Meanwhile, the village economy was still in ‘sufficient’ category and still undeveloped. They were not able to improve the developed economy system. Also, the post-harvest activities of some people were selling agricultural products for their daily needs, and they had industrial activities, such as making crafted bags from yarn and making ‘kupang parang’ from wood to increase their incomes to fulfill their needs.This study concluded that the way of farming of the farming community was ‘bero’ which is a system of having a break time and a one-year harvest system; the economy of farming communities was in sufficient category that their incomes were just enough to fulfill their daily needs only; the postharvest activities of farming communities were gardening, crafted bag making, and ‘kupang’ machete making and also machete handles from mostly wood.Keywords: economy, society, and farmers